PENGARUH KOMITMEN ORGANISASI, PERAN KEPEMIMPINAN, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJAPEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA BINJAI. - Viska Yanti (Manajemen dan Bisnis, 2020)
The problem in this research is: how the influence of organizational commitment on employee performance at the Binjai Pratama Tax Office. How does the role of leadership influence employee performance, how does motivation influence employee performance, how does job satisfaction affect employee performance, how does organizational commitment influence, role leadership, motivation and job satisfaction on employee performance at the Binjai Pratama Tax Office. The hypothesis proposed is: Organizational commitment has a positive and significant effect on employee performance, the role of leadership has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, organizational commitment, leadership role, motivation and job satisfaction have a positive and significant effect on employee performance at the Binjai Pratama Tax Office .. ". The study was conducted at the Binjai Pratama Tax Office. Jambi Road No. 1 Rambung Barat Binjai City North Sumatra, 20722, with a sample of 82 people. Based on the analysis results obtained there is a significant effect between work ability on employee performance, because according to the results of the analysis of t count t-table (2.966 1.67) at n = 96 with a significance level of 95%. There is a significant influence between organizational culture on employee performance, the results of t analysis t-table (3.220 1.67) at n = 96 with a significance level of 95%. There is a significant influence between organizational climate on employee performance, because according to the results of the analysis of t count t-table (1.984 1.67) at n = 96 with a significance level of 95%. There is a significant influence between loyalty on employee performance, because according to the results of the analysis of tcount t-table (8,893 1.67) at n = 96 with a significance level of 95%. F-count value F table (87,303 2.46) with dk numerator 4 and dk denominator 91 together (multiple) there is a positive and significant influence of work ability, organizational culture, organizational climate and loyalty to the performance of employees of the West Medan Pratama Tax Office. Thus the hypothesis proposed is accepted.